2016
DOI: 10.4049/jimmunol.1600508
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Expansion of Endogenous Regulatory T Cell Populations Induces Long-Term Suppression of Contact Hypersensitivity

Abstract: Contact hypersensitivity (CHS) of murine skin serves as a model of allergic contact dermatitis. Hapten-specific CD8 T cells and neutrophils represent the major effector cells driving this inflammatory reaction whereas Foxp3+ regulatory T cells (Tregs) control the severity of inflammation. However, whether in vivo expansion of endogenous Tregs can downregulate CHS-mediated inflammation remains to be elucidated. In this study, we addressed this issue by using injection of an IL-2/anti–IL-2 mAb JES6-1 complex (IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
0
17
1
Order By: Relevance
“…Gomez de Aguero et al reported that Langerhans cells (cutaneous dendritic cells) are critical in the regulatory process through inducing the depletion of antigen‐responsive T cells and by activating FOXP3 + Tregs. Furthermore, in vivo expansion of Treg populations has been shown to induce long‐term suppression of contact hypersensitivity . In humans, Cavani et al have reported that CD25 + regulatory T cells maintain tolerance to the contact metal allergen nickel in nonhypersensitive individuals.…”
Section: Regulatory T Cells (Tregs)mentioning
confidence: 99%
“…Gomez de Aguero et al reported that Langerhans cells (cutaneous dendritic cells) are critical in the regulatory process through inducing the depletion of antigen‐responsive T cells and by activating FOXP3 + Tregs. Furthermore, in vivo expansion of Treg populations has been shown to induce long‐term suppression of contact hypersensitivity . In humans, Cavani et al have reported that CD25 + regulatory T cells maintain tolerance to the contact metal allergen nickel in nonhypersensitive individuals.…”
Section: Regulatory T Cells (Tregs)mentioning
confidence: 99%
“…El Beidaq et al . demonstrated that tolerance to CHS mediated by TNCB can be enforced by injection of an IL-2/anti-IL-2 antibody reagent, IL-2/JES6-1 58 . This treatment, when given before or even after sensitization, established a state of tolerance by CTLA4 + Foxp3 + Treg expansion that was still evident upon re-challenge with contact allergen even 3 weeks after the last injection.…”
Section: Immune Regulation and Tolerance To Contact Allergensmentioning
confidence: 99%
“…Allergic contact dermatitis (ACD) is a T-cell-mediated delayed hypersensitivity reaction characterized by the occurrence of inflammatory skin lesions following contact with a particular allergen. 1 Nonprotein allergens, or haptens, capable of eliciting contact dermatitis include a wide range of substances encountered within occupational or domestic settings. 2 ACD has a reported median prevalence of approximately 20% across Europe and North America and is continuing to increase with limited therapeutic options addressing its burden.…”
Section: To the Editormentioning
confidence: 99%
“…5 In this study, we used the CC to investigate the genetic factors underlying CHS, the murine model of ACD in which hapten sensitization and subsequent immune challenge can be fully controlled and standardized. 1,2 We assessed CHS in 38 strains of CC mice by measuring the increase in ear thickness at various time points after a single standardized oxazalone challenge (see this article's Methods section in the Online Repository at www.jacionline.org). At each time point, there were marked differences in response between CC strains in both the acute response to immune challenge and postchallenge recovery (see Results and Discussion sections and Fig E1 in this article's Online Repository at www.jacionline.org).…”
Section: To the Editormentioning
confidence: 99%